2021
DOI: 10.1038/s41467-021-25366-0
|View full text |Cite
|
Sign up to set email alerts
|

Neural signatures of hyperdirect pathway activity in Parkinson’s disease

Abstract: Parkinson’s disease (PD) is characterised by the emergence of beta frequency oscillatory synchronisation across the cortico-basal-ganglia circuit. The relationship between the anatomy of this circuit and oscillatory synchronisation within it remains unclear. We address this by combining recordings from human subthalamic nucleus (STN) and internal globus pallidus (GPi) with magnetoencephalography, tractography and computational modelling. Coherence between supplementary motor area and STN within the high (21–30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
93
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 78 publications
10
93
0
1
Order By: Relevance
“…Furthermore, we found that the HD pathway shifts beta rhythms to higher frequencies in line with the hypothesis that β 2 activity is a signature of cortico-subthalamic drive, following the finding a correlation between β 2 power and HD tract density in PD patients [40]. Whether β 1 or β 2 bands reflect functionally distinct rhythms is not well understood-lower frequency activity is more readily suppressed by Levodopa [18] and DBS [38], and STN activity in the two sub-bands synchronize with different cortical regions [38,39].…”
Section: Different Network States Underlie the Expression Of Oscillat...supporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, we found that the HD pathway shifts beta rhythms to higher frequencies in line with the hypothesis that β 2 activity is a signature of cortico-subthalamic drive, following the finding a correlation between β 2 power and HD tract density in PD patients [40]. Whether β 1 or β 2 bands reflect functionally distinct rhythms is not well understood-lower frequency activity is more readily suppressed by Levodopa [18] and DBS [38], and STN activity in the two sub-bands synchronize with different cortical regions [38,39].…”
Section: Different Network States Underlie the Expression Of Oscillat...supporting
confidence: 87%
“…Nonetheless, model fits did not well reproduce the broadband high frequency activity present in the data (Fig 1B ; inset spectra). The model also produced activity at two subpeaks at lower (β 1 : 14-21 Hz) and upper (β 2 : 21-30 Hz) beta frequencies, reflecting the bimodal structure of directed functional connectivity (see analysis of multiple Gaussian fits to features from individual animals; S2 Fig) , and in line with experimental reports of a functionally related subdivision of the beta band [39,40].…”
Section: A Data Constrained Model Of the Cortico-basal Ganglia-thalam...supporting
confidence: 79%
See 1 more Smart Citation
“…Our anatomical results suggest that this propagation may be specific to dorsal STN. Slowness decoding models alternatively relied upon β activity in macroelectrode recordings, perhaps reflecting anti-kinetic β bursts relayed to ventral STN from inferior frontal or supplementary motor cortex (31, 32) . But while prior work did not directly compare the neuroanatomical substrate of distinct PD features within or across subjects, this work directly demonstrates how alternating motor features of PD manifest along these anatomical subdivisions.…”
Section: Discussionmentioning
confidence: 99%
“…3D). Power in γ low frequencies (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) in particular was found to be significantly increased during effective motor control relative to both tremor and slowness decoding models ( p<0.006, permutation test) (Fig. 3E-F, right).…”
Section: Effective Motor Control Had Characteristic Neural Signaturesmentioning
confidence: 95%